A genetic-algorithm-based approach for audio steganography - Zamani, Mazdak; Abdul Manaf, Azizah; Ahmad, Rabiah; Zeki, Akram M.; Abdullah, Shahidan (World Academy of Science, Engineering and Technology (W A S E T), 2009)
In this paper, we present a novel, principled approach to resolve the remained problems of substitution technique of audio steganography. Using the proposed genetic algorithm, message bits are embedded into multiple, vague and higher LSB layers, resulting in increased robustness. The robustness specially would be increased against those intentional attacks which try to reveal the hidden message and also some unintentional attacks like noise addition as well.